A STUDY OF LEARNING ENVIRONMENT IN MATHEMATICS CLASSROOM AT THE PRIMARY LEVEL - BHATIA, KUSUM (THE PRIMARY TEACHER, 2013)
The Right of Children to Free and Compulsory Education Act is in force since April, 2010. It has generated a series of huge challenges on one hand and provided enormous opportunities for the country on the other. As states think about how to admit children currently out of school into the age-appropriate grade, it is imperative to think about how to help the thousands of children who are already in school achieve the levels of learning appropriate to their grade. The time is right to think about what our schools can do to ensure not just schooling, but guaranteed learning to every child. This is the Right to Education 2009 (RTE) Act, in its true spirit. Parents all over the country are pinning their hopes on education as the cornerstone to a better life for their children. However, this sort of rethinking requires a realistic assessment of the state of affairs and going beyond an evaluation of the inputs that are provided to our children in schools in terms of classrooms, teachers, teaching-learning process and learning environment. There is a need to study the ways in which these inputs are organised and used by schools vis-a-vis what has been suggested in National Curriculum Framework-2005.